2016
DOI: 10.1016/j.jpainsymman.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Trial of a Telephone Symptom Management Intervention for Symptomatic Lung Cancer Patients and Their Family Caregivers

Abstract: Context Lung cancer is one of the most common cancers affecting both men and women and is associated with high symptom burden and psychological distress. Lung cancer patients’ family caregivers also show high rates of distress. However, few interventions have been tested to alleviate significant problems of this population. Objectives This study examined the preliminary efficacy of telephone-based symptom management (TSM) for symptomatic lung cancer patients and their family caregivers. Methods Symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 74 publications
(82 reference statements)
1
115
0
8
Order By: Relevance
“…On the other hand, the second cluster concerning carer's relationship with the patient evaluated perceived support such as difficulties encountered in communicating with the patient about the disease, and caregiver's perception of patient's symptom management [51,55,70]. The Edmonton Symptom Assessment Scale (ESAS) was the main tool used to assess these variables.…”
Section: Measured Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the second cluster concerning carer's relationship with the patient evaluated perceived support such as difficulties encountered in communicating with the patient about the disease, and caregiver's perception of patient's symptom management [51,55,70]. The Edmonton Symptom Assessment Scale (ESAS) was the main tool used to assess these variables.…”
Section: Measured Outcomesmentioning
confidence: 99%
“…These improved outcomes were: caregiver self-efficacy, Quality of Life, distress, depression, appraisal of caregiving, and perceived social support. Caregiver self-efficacy both in managing own emotions and in helping the patients to control symptoms was measured in five studies [52,59,61,67,70] and was always statistically significant. Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being.…”
Section: Measured Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also been conducted on psychological distress among nursing students [87] and drug users [88][89]. Psychological distress have also been investigated among caregivers particularly of people with chronic obstructive pulmonary disease [90], patients with psychosis [91][92], patients with schizophrenia [93], cancer patients [94], symptomatic lung cancer patients [95], women with ovarian cancer [96], patients with lung cancer [97][98], and individuals with affective disorders [99]. Studies on psychological distress have also been done on caregivers of children with autism spectrum disorder [100][101][102][103] and children with asthma [104], children with a disorder of sex development [105][106].…”
Section: Statement Of the Problemmentioning
confidence: 99%